Chemical composition of Phasey Bean (Macroptilium Lathyroides (L.) Urb.) (Research, Society and Development, 2020)
The objective of the study was to determine the chimical composition of phasey bean throughout the productive cycle. The experiment was carried out in the municipality of Capão do Leão – RS, physiographic south coast region of Rio Grande do Sul. At 45 days after the emergence of the plants, the first cut of the forage evaluation was performed and, at intervals of 15 days, another nine cuts were made, all 5 cm from the soil. The treatments corresponded to different evaluation dates of Macroptilium in free growth in an experiment with ten treatments and three replicates in a completely randomized design. The variables studied were neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), crude protein (PB), total lipids (TL), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg). The results were submitted to analysis of variance and polynomial regression. All variables presented significance (P≤0.05) for cubic regressions, with mean values of: NDF = 58.15; FDA = 38.94; ADL = 9.15; PB = 11.59; TL = 1.18% e; P = 2.29; K = 10.19; Ca = 26.48 and Mg = 4.53 g / kg DM; similar to other hot-legged forage legumes. The bromatological quality of the Macroptilium lathyroides varied during the productive cycle, being directly influenced by the habit of indeterminate growth of the species. From the bromatological quality, the forage of the first growth of the Macroptilium lathyroides should be harvested up to 75 days after emergence, when the lower fiber and lignin contents associated with higher levels of crude protein, lipids, magnesium, and calcium.